Pharmacy students’ interprofessional experience and performance in advanced pharmacy practice experience rotations amid COVID-19 pandemic - Alrasheed, Marwan; Alsuhibani, Abdulrahman; Alotaibi, Wadha; Gari, Musaab; Alashgar, Amin; Doherty, Michael; Boone, Jill; Almangour, Thamer A.; Hincapie, Ana (Frontiers in Medicine, 2024)
Introduction: Interprofessional education (IPE) is essential in pharmacy training, providing students with vital collaborative skills for real-world healthcare. Advanced Pharmacy Practice Experience (APPE) is integral to IPE, allowing students to apply their knowledge in diverse healthcare settings. The COVID-19 pandemic has disrupted healthcare education and raised concerns about its impact on IPE during APPE rotations. Our study investigates the pandemic's influence on pharmacy students' interprofessional interactions and APPE performance. Objective: To assess the interprofessional experiences of fourth-year pharmacy students before and during the COVID-19 pandemic in the context of APPE. Methods: This retrospective observational study examined the experiences of P4 pharmacy students in the USA during APPEs before and during the pandemic. We employed electronic surveys with 21 questions to gauge interactions and interprofessional team effectiveness, employing Likert scale response options. We compared responses between the 2019-2020 and 2020-2021 APPE rotations using statistical tests.Results: Our study encompassed 83 and 86 students for the 2019-2020 and 2020-2021 APPE rotations, respectively, achieving a 100% response rate. Amid the pandemic, written communications between pharmacy students and healthcare providers in general medicine rotations increased, while in-person engagement decreased. Pre-COVID, students reported higher colleague referrals and greater interprofessional utilization during ambulatory care rotations.Conclusions: COVID-19 shifted interactions from in-person to written communication between pharmacy students and healthcare providers. Students reported decreased satisfaction with their interprofessional experiences. This research offers insights into the changing landscape of pharmacy education, helping students prepare for evolving challenges in healthcare delivery and education.